Pediatric Medical Devices ― Survey of Pediatric Cardiologists and Cardiovascular Surgeons in Japan ― - Miyoshi, Takekazu (Circ Rep, 2021)
Background: In Japan, the choice of pediatric medical devices is limited because of 2 “device lag” problems: Japan lags behind the USA and Europe in device development, and development of pediatric devices lags behind that of adult devices. We aimed to identify the problems with and impediments to pediatric medical device development as recognized by pediatric physicians in Japan. Methods and Results: A voluntary survey of pediatric medical devices for all council members of the Japanese Society of Pediatric Cardiology and Cardiac Surgery was conducted in 2019. The response rate was 47.1% (154/327). The respondents were 115 pediatric cardiologists (74.7%) and 39 cardiovascular surgeons (25.3%). Approximately 90% believed that difficulties in development existed. Approximately 70% were dissatisfied with the pediatric medical devices currently available in Japan, which was a result of the unavailability of medical devices approved overseas, few types and sizes, and off-label use. Factors that hindered the development of pediatric medical devices included anatomical issues specific to children with congenital heart disease, as well as system issues such as lack of corporate profitability, development cost, and amount of time for development. Conclusions: Pediatric cardiologists and cardiovascular surgeons regard “device lag” and “off-label use” in Japan as important hindrances to the delivery of better medical care for pediatric patients with congenital heart disease.